Prevalence of Anemia among Pregnant Women Attending Primary Health Care Center in Bab-Al-Moudham - Athraa karim Hussein; Shatha Mahmood Niazy; Buthaina Ateyah Rashid; Ban yousuf yaqcoob; Abeer abdul-Razzak; Maithem Nasser Ahmed (Diyala Journal of Medicine, 2019)
Background: Anemia is define as decreased hemoglobin level, or circulating red blood cells and it is the most common hematological disorder during pregnancy.